ANTI-CRISIS MANAGEMENT OF THE SOCIO-ECONOMIC SYSTEMS UNDER THE POST-WAR PERIOD UNCERTAINTY - TYURINA, Nila; NAZARCHUK, Tatiana; HURNYTSKYI, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyses main indicators reflecting the state of Ukraine's economy during the war. We studied the core approaches to the formation of economic policy, development strategy and management of Ukraine economy in the pre-war period. The priorities of the country’s modern economic policy were defined and the necessary structural changes of the national economy, the main components of impact on its effective development in the post-war period, were determined. The goals and content of the post-war recovery plan for Ukraine's economy were studied. Strategically important industries for the post-war economy of Ukraine, attractive directions for foreign investment and the main components of recovery and development were defined: international support, effective investment policy, modern reorganisation and restructuring of the economy. In order to get out of the micro-level socio-economic systems crisis primary measures of the anti-crisis plan have been formed. Three stages of the crisis have been identified and tasks and functions for the anti-crisis team of business structures have been specified. Changes in HR management in the anti-crisis management system of business entities in the war and post-war periods were analysed, the most important modern anti-crisis HR tools were formulated and characterised.
Keywords: crisis; development; economy; management; HR management